Customer reactions and competitive responses to mergers in a B2B service industry - Kato, Junichi (Cranfield University, 2012)
The primary aim of this doctoral research was to empirically investigate customer and competitive reactions to post-M&A integration through both quantitative and qualitative customer perspectives, and to identify the business impact of these reactions and its potential causal mechanisms. The topic is widely recognised among practitioners but has received relatively little attention in the academic literature (Anderson et al., 2001; Schweiger and Very, 2003), which might explain the reason why decisive factors for M&A success are still elusive (Homburg and Bucerius, 2005). The research was carried out in three stages. Project-1 engaged in a systematic review of the marketing literature in order to build a foundation of knowledge on customer-supplier relationships. The review results were integrated into a literaturebased conceptual model, indicating the link between customer relationship management activities, customer loyalty and company performance, under ‘business as usual’ conditions. Based on this conceptual model, Project-2 empirically investigated post-M&A business issues through a single case study of multi-business mergers. Interviews with key account managers and their customers suggested a potential underlying causal mechanism of integration effects on customer-supplier relationships. Finally, Project-3 tested the key variables and interrelationships identified in Project-2 through a survey method in order to begin the process of generalization. Survey responses from business-to-business (B2B) customers were analysed by applying Structural Equation Modelling, which indicated potential causal correlations between integration activities, perceived changes in customer relationship variables and changes in the level of behavioural customer loyalty during the post-M&A period. The findings suggest a possible answer to the overall research question — what are the key factors that affect post-M&A business performance, or more specifically, what are the key variables that influence customer reactions and why/how? Post-M&A integration actions were found to trigger customer relationship issues. For instance, the integration of operations and IT systems leads to perceived deterioration in service performance, while salesforce integration creates organisational issues such as employees’ internally focused attitudes, which result in perceived declines in customer orientation and account management quality. Furthermore, integration actions as a whole generate an unstable business environment that promotes intensive competitive attacks. Some contextual factors which magnify these issues were also identified, specifically the complexity of the merger/integration and the depth of the pre-merger customer relationships. The issues above negatively influence customers’ purchase intentions and, in the worst cases, drove customers to terminate contracts, which would exert a negative impact on the merging parties’ business performance during the post- M&A integration period. The research has made a step towards a better understanding of how customers and competitors respond to post-M&A integration and the mechanisms by which those responses arise, particularly within the focal industry context of this study. It contributes to the M&A-integration and performance literature by illuminating the role and drivers of competitive attacks, and customer reactions in determining market-related M&A performance. It also contributes to the M&A-integration and business network literature by suggesting the mechanisms through which the customer-supplier relationship is impacted by post-M&A integration activities. Finally, contributions to practice and methodological development, as well as limitations and implications for future research, are also presented.